2018
DOI: 10.1108/par-04-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the usefulness of management accounting systems in integrated manufacturing environment

Abstract: Purpose This paper aims to report the results of a study investigating the mediating role of managerial use of management accounting system (MAS) information in the relationship between integrated manufacturing practices (IMPs) and organisational performance (OP). IMP comprises three manufacturing practices, namely, just in time (JIT), total quality management (TQM) and advanced manufacturing technologies (AMTs). Design/methodology/approach Using a mailed questionnaire, the data were gathered from senior man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 49 publications
(80 reference statements)
7
55
1
2
Order By: Relevance
“…This result indicates that the use of sophisticated MAS causes improvement in managerial performance. This finding is consistent with previous researches in management accounting (Baines and Langfield-Smith, 2003;Etemadi et al, 2009;Hammad et al, 2010;Hoque, 2011;Ismail and Isa, 2011;Rasid et al, 2011). Relating to different MAS characteristics, the findings of the relationship between scope and performance (H2a), between timeliness and performance (H2b), and between aggregation and performance (H2d) provide further support for Hypothesis 2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result indicates that the use of sophisticated MAS causes improvement in managerial performance. This finding is consistent with previous researches in management accounting (Baines and Langfield-Smith, 2003;Etemadi et al, 2009;Hammad et al, 2010;Hoque, 2011;Ismail and Isa, 2011;Rasid et al, 2011). Relating to different MAS characteristics, the findings of the relationship between scope and performance (H2a), between timeliness and performance (H2b), and between aggregation and performance (H2d) provide further support for Hypothesis 2.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, a conditional association presumes that useful information helps managers in making effective decisions, which improves managerial performance (Baines and Langfield-Smith, 2003;Chenhall, 2003;Hammad et al, 2010). Therefore, the use of MAS information by managers can assist them in making more accurate decision, which will lead to improvement in performance (Ismail and Isa, 2011).…”
Section: Relationship Between Mas and Managerial Performancementioning
confidence: 99%
“…Fullerton and Wempe (2009) also demonstrated that the use of broad scope MAS information that provides non-financial information on manufacturing performance assists firms to improve financial performance in lean manufacturing environment. Using a sample of Malaysian manufacturing firms, Ismail and Isa (2011) demonstrated that the use of broad scope MAS information mediates the relationship between Advanced Manufacturing Technology (AMT) and performance. In addition, Fullerton, Kennedy and Widener (2014) documented that lean manufacturing practices also indirectly affect operations performance through lean management accounting practices (MAP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fullerton, Kennedy and Widener (2014) documented that lean manufacturing practices also indirectly affect operations performance through lean management accounting practices (MAP). More recently, Ismail, Isa and Mia (2018) showed that MAS information helps manufacturing firms in Malaysia that adopt Integrated Manufacturing Practices to improve performance.…”
Section: Introductionmentioning
confidence: 99%
“…Great design of MAS helps managers to be more efficacious in decision making, thereby aiding organization improving their efficiency and become more competitive toward any challenging environment. This definitely improves the performance of organizations (Ismail and Isa, 2011 (Winter, 2007). We can observe that there is a growing body of literature that examines the effect of MAS and performance as well as RM and organizational performance, the knowledge of linkage method MAS and RM that can reinforce the banks performance remains a gap.…”
Section: Introductionmentioning
confidence: 99%